Adrenal βarrestin1 targeting for tobacco–associated cardiac dysfunction treatment: Aldosterone production as the mechanistic link. Issue 4 (18th June 2019) - Solesio, Maria E; Mitaishvili, Erna; Lymperopoulos, Anastasios
Abstract: Tobacco kills 6 million people annually and its global health costs are continuously rising. The main addictive component of every tobacco product is nicotine. Among the mechanisms by which nicotine, and its major metabolite, cotinine, contribute to heart disease is the renin‐angiotensin‐aldosterone system (RAAS) activation. This increases aldosterone production from the adrenals and circulating aldosterone levels. Aldosterone is a mineralocorticoid hormone with various direct harmful effects on the myocardium, including increased reactive oxygen species (ROS) generation, which contributes significantly to cardiac mitochondrial dysfunction and cardiac aging. Aldosterone is produced in the adrenocortical zona glomerulosa (AZG) cells in response to angiotensin II (AngII), activating its type 1 receptor (AT1 R). The AT1 R is a G protein‐coupled receptor (GPCR) that leads to aldosterone biosynthesis and secretion, via signaling from both Gq/11 proteins and the GPCR adapter protein βarrestin1, in AZG cells. Adrenal βarrestin1 is essential for AngII–dependent adrenal aldosterone production, which aggravates heart disease. Since adrenal βarrestin1 is essential for raising circulating aldosterone in the body and tobacco compounds are also known to elevate aldosterone levels in smokers, accelerating heart disease progression, our central hypothesis is that nicotine and cotinine increase aldosterone levels to induce cardiac injury by stimulating adrenal βarrestin1. In the present review, we provide an overview of the current literature of the physiology and pharmacology of adrenal aldosterone production regulation, of the effects of tobacco on this process and, finally, of the effects of tobacco and aldosterone on cardiac structure and function, with a particular focus on cardiac mitochondrial function. We conclude our literature account with a brief experimental outline, as well as with some therapeutic perspectives of our pharmacological hypothesis, that is that adrenal βarrestin1 is a novel molecular target for preventing tobacco–induced hyperaldosteronism, thereby also ameliorating tobacco–related heart disease development.